Gilberto Freyre: indiciarismo, emoção e política na casa-grande e na senzala - Coelho, Claudio Marcio (2007)
This essay proposes an investigation on the interdependent relationship between the evidential paradigm theory, emotion and politics in Gilberto Freyre’s thinking, in the period that goes from his childhood (1906) to the publication of his germinal work Casa-Grande & Senzala (1933). The author used scientific parameters of the comprehensive analysis – by valuing the subjective character of knowledge –, the social microanalysis – by analyzing the peculiarities of the phenomena studied –, and the clues analysis – by investigating revealing details – in the historical and sociological study of childhood in Brazil. His theoretical and methodological pluralism was based on principles and procedures of the Evidential Paradigm Theory. A detailed search of the life and work of the author was carried out by means of complementary methods: the history of the reading (Intellectual Biography), the detailed and exhaustible field research (Ethnography), and clues analysis (Evidential Paradigm Theory). Freyre’s preference for the details of everyday life and intimacy, as well as his emotional and poetic narrative of the events, have definitely influenced the elaboration of an original political view: the relationship of violence, love and hatred between the white and the black, the master and the servant, the sadistic and the masochistic has generated feelings and emotions that explain the continuity of the abuse of power, authoritarianism, and subservience in the Brazilian political history.